2013
DOI: 10.1098/rspb.2013.1151
|View full text |Cite
|
Sign up to set email alerts
|

Processing power limits social group size: computational evidence for the cognitive costs of sociality

Abstract: ResearchCite this article: Dávid-Barrett T, Dunbar RIM. Sociality is primarily a coordination problem. However, the social (or communication) complexity hypothesis suggests that the kinds of information that can be acquired and processed may limit the size and/or complexity of social groups that a species can maintain. We use an agent-based model to test the hypothesis that the complexity of information processed influences the computational demands involved. We show that successive increases in the kinds of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 46 publications
2
58
0
Order By: Relevance
“…In this work, we focus on 1.5 ego-networks as they capture a reasonable level of social context (me, my friends, and the relationships between them) while still keeping the data requirements and computational complexity low. This is in congruence with the human processing limits and the social brain hypothesis proposed by Dunbar et al [5] and also the recent results that have shown the value of 1.5 ego networks in identifying network phenomena [1].…”
Section: Characterizing Social Structure Surrounding Bullying Messagessupporting
confidence: 84%
“…In this work, we focus on 1.5 ego-networks as they capture a reasonable level of social context (me, my friends, and the relationships between them) while still keeping the data requirements and computational complexity low. This is in congruence with the human processing limits and the social brain hypothesis proposed by Dunbar et al [5] and also the recent results that have shown the value of 1.5 ego networks in identifying network phenomena [1].…”
Section: Characterizing Social Structure Surrounding Bullying Messagessupporting
confidence: 84%
“…In this work, we focus on building 1.5 ego networks as they capture a reasonable level of social context (me, my friends, and the relationships between them) while still keeping the data requirements and computational complexity low. This is in congruence with the human processing limits and the social brain hypothesis proposed by [63] and also the recent results that have shown the value of 1.5 ego networks in identifying network phenomena [62].…”
Section: Characterizing Social Structure Surrounding Bullying Messagessupporting
confidence: 72%
“…In contrast, we focus on the extent to which such decisions affect network cohesion and the indirect effects that this has on individual fitness. This approach shares with the models developed by Dávid-Barrett & Dunbar [23,46,47] a focus on achieving behavioural synchrony as an intermediate goal necessary for maximizing fitness, in line with Hamilton's conception of neighbourhood modulated fitness [29,30]. More importantly, it bypasses the conventional collective action dilemma created by free-riders because it is not possible to free-ride: one is either in the group or one is not, and one benefits accordingly [46].…”
Section: Introductionmentioning
confidence: 80%